EU cybersecurity and cyber diplomacy - Agnes Kasper; Anna-Maria Osula; Anna Molnár (IDP, 2021)
Over the last decades cybersecurity has become a cornerstone of European digital development. Alongside with the diffusion of information and communication technologies and the deepening (as well as widening) of the European Union, the initial narrow and sectoral data security policies have expanded into a comprehensive cybersecurity framework addressing issues from resilient infrastructure and technological sovereignty, through tackling cybercrime, to cyber defence capabilities and responsible state behaviour in cyberspace. In this complex web of interrelated policies a relative newcomer at the European Union (EU) level is cyber diplomacy. Sometimes also called public diplomacy 2.0, it factors into the cross-border connectivity of cyberspace and reflects a shift in international relations where the lines between external and internal policies, military and civilian domains are blurred. However, the term cyber diplomacy is fluid and it is not well understood which topics should be under its “umbrella”, in particular in relation to cybersecurity, where it seems to be linked the most. This article aims to map existing and proposed instruments that make up the EU’s arsenal in this broad context to answer the following questions: what is cyber diplomacy and how is it related to the EU cybersecurity? Is cyber diplomacy in the EU becoming something in its own right as a distinct set of tools to secure the EU policy objectives?